IUS Constituendum Of Cross-Border Insolvency Regulation In Asean (Analysis Of The Uncitral Model Law On Cross-Border Insolvency And The European Union Regulation On Insolvency Proceedings) - Andrian Andrian; Gunardi Lie (Eduvest - Journal of Universal Studies, 2024)
Currently, ASEAN has an economic integration program that is stated in the ASEAN Economic Community Blueprint. As is well known, the European Union is the only regional organization that has succeeded in creating economic integration in its region supported by a unified law. One of the legal unification that needs to be initiated by ASEAN in supporting its economic integration is cross-border insolvency regulation. Some international legal instruments that can be a reference for the establishment of the ASEAN Cross-border Insolvency Regulation include the UNCITRAL Model Law on Cross-Border Insolvency and EU Regulation 848/2015 on Insolvency Proceedings. However, the comparison between ASEAN and the EU is not equivalent. ASEAN is a regional organization that is intergovernmental in nature, while the EU is a regional organization that is supranational in nature. Therefore, the comparative approach and statute approach are the right approaches in this article's writing. As for the research method used in this article writing is normative research. The objectives of this article are to describe the legal personality of ASEAN and the European Union in relation to the establishment of cross-border insolvency regulation and provide an overview of the substance of the UNCITRAL Model Law on Cross-Border Insolvency and EU Regulation 848/2015 to provide a reference for ASEAN to from cross-border insolvency regulation.